2020
DOI: 10.14744/etd.2019.33349
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of anterior segment parameters and specular microscopy findings in patients with COPD

Abstract: Objective:The aim of the present study was to assess the anterior segment parameters of patients with chronic obstructive pulmonary disease (COPD) by corneal specular microscopy and biometry and to compare the results with healthy controls. Materials and Methods:Our prospective study consisted of 122 eyes of 61 patients with COPD and 110 eyes of 55 patients without any systemic diseases. A comprehensive medical history was obtained, and corrected visual acuity, bio microscopic and fundus examination, intraocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, they found no difference in CT between those COPD groups. 12 Sayin et al examined the effect of smoking on dry eye and corneal endothelial parameters and reported that the Schirmer score, tear breakup time (TBUT) value, and the ratio of hexagonal cells in the corneal endothelium were lower in smokers. However, no difference was found between the two Abbreviations: CD, the cell density in the corneal endothelium (cell/mm 2 ); CT, corneal thickness (µ); CV, coefficient of variation (the cell area standard deviation/mean cell area, µm 2 ); HEX, percentage of hexagonal cells (%).…”
Section: Discussionmentioning
confidence: 99%
“…However, they found no difference in CT between those COPD groups. 12 Sayin et al examined the effect of smoking on dry eye and corneal endothelial parameters and reported that the Schirmer score, tear breakup time (TBUT) value, and the ratio of hexagonal cells in the corneal endothelium were lower in smokers. However, no difference was found between the two Abbreviations: CD, the cell density in the corneal endothelium (cell/mm 2 ); CT, corneal thickness (µ); CV, coefficient of variation (the cell area standard deviation/mean cell area, µm 2 ); HEX, percentage of hexagonal cells (%).…”
Section: Discussionmentioning
confidence: 99%